2016
DOI: 10.1142/s0219581x16500125
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Neodymium Oxide Nanoparticle-Doped Polyvinyl Alcohol Film

Abstract: The structural and optical characteristics of polyvinyl alcohol (PVA) doped with di®erent concentration of Nd 2 O 3 nanoparticles to use an active media for polymer laser were studied. The PVA polymer was considered as the host and Nd 2 O 3 nanoparticles as the active element. The media as a thin¯lm was prepared using spin coating technique. Structural properties of layers were investigated by X-ray di®raction (XRD) pattern and atomic force microscope (AFM) technique. The e®ect of the concentrations of the neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Furthermore, the growing literature has provided a study on the optical properties of PVA containing several rare-earth sources. For example, Keikhaei et al investigated the optical properties of PVA with Nd 2 O 3 using UV-Vis absorption spectroscopy [ 11 ]. Meanwhile, polyvinyl pyrrolidone (PVP) is an excellent polymer which was designed to be a coating and additive to several materials [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the growing literature has provided a study on the optical properties of PVA containing several rare-earth sources. For example, Keikhaei et al investigated the optical properties of PVA with Nd 2 O 3 using UV-Vis absorption spectroscopy [ 11 ]. Meanwhile, polyvinyl pyrrolidone (PVP) is an excellent polymer which was designed to be a coating and additive to several materials [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…2. It can be observed that the broadband at 3455 cm − 1 for pure oxide while adding silver NPs does not cause a noticeable shift that O-H stretching vibration of the -OH group appears at 3448 cm − 1 [14]. The revealing absorption peak at 3554 cm − 1 is attributed to thio-urea residual N-H stretching [15].…”
Section: Ftirmentioning
confidence: 92%
“…The revealing absorption peak at 3554 cm − 1 is attributed to thio-urea residual N-H stretching [15]. The Neodymium oxide (Nd 2 O 3 ) NPs strong band centered at 669 cm − 1 is attributed to Nd-OH which shows signi cant diminishing with adding Silver nano-particles [14]. The centered bands at 588 cm − 1 was because of -O stretching of Nd [13].…”
Section: Ftirmentioning
confidence: 98%
“…Thus in principle, it is recommended to use materials with low absorption at the emission and pump wavelength. As a result, polymeric materials have been newly considered as an attractive host matrix for rare earth ions due to their unique properties, including reasonable cost, straightforward fabrication procedure, excellent precise refraction coefficients, well thermal stabilities, as well as great transparency in wide-ranged spectral regions (visible and near-infrared) [4,5].…”
Section: Introductionmentioning
confidence: 99%